Construction of a System of Relief Channels for Maladministration - Yuting Zeng (Studies in Law and Justice, 2024)
As society develops and the functions of administrative organs continue to expand, the phenomenon of violations of citizens’ rights is emerging, and the awareness of citizens’ rights is awakening. There is a growing demand for remedies not only for administrative violations, but also for administrative malpractices that violate rights. By reorganizing and integrating the relief channels, explore the advantages and disadvantages of different relief channels, build appropriate and effective relief mechanism. When administrative disputes arise from maladministration in administrative management activities, citizens can choose appropriate relief channels under the premise of following the principle of giving priority to intra-administrative remedies and final judicial remedies to effectively supervise administrative conduct and protect their rights and interests. China’s current system of relief channels for maladministration is a diversified and multi-level system of remedies with openness, with administrative reconsideration as the main channel, and with the traditional channels of administrative reconsideration, administrative litigation, letters and visits, and complaints and reports on administrative law enforcement as the basic channels, supplemented by the new channels of microblogging, mayor’s public telephone calls, and reception days for the head of the government, which will be enriched and improved over time and with the development of society.